Faktor-Faktor yang memengaruhi Corporate Social Responsibility Disclosure - Verina Gladiola; Ricardo Suhendra Wirjawan (Media Bisnis, 2021)
This study aims to obtain emprical evidence regarding the effect of foreign ownership, managerial ownership, institutional ownership, audit committee, board of commisioner size and leverage on the disclosure of corporate social responsibility. The company used in this research is manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2018-202. The method used in this research is purposive sampling and there are 49 companies and 136 data used in this research. This research uses multiple regressionn method in conducting data analysis. The result of the research stated that the variables of foreign ownership, audit committee, board of commisaries size and leverage have an influence disclosure of corporate social responsibility. While the variable of managerial ownership and intitutional ownership have no effect on disclosure of corporate social responsibility.